The inactive X chromosome is epigenetically unstable and transcriptionally labile in breast cancer - Chaligné, Ronan; Popova, Tatiana; Mendoza-Parra, Marco-Antonio; Saleem, Mohamed-Ashick M.; Gentien, David; Ban, Kristen; Piolot, Tristan; Leroy, Olivier; Mariani, Odette; Gronemeyer, Hinrich; Vincent-Salomon, Anne; Stern, Marc-Henri; et al.

(untitled) (Genome Research, 2015)
Disappearance of the Barr body is considered a hallmark of cancer, although whether this corresponds to genetic loss or to epigenetic instability and transcriptional reactivation is unclear. Here we show that breast tumors and cell lines frequently display major epigenetic instability of the inactive X chromosome, with highly abnormal 3D nuclear organization and global perturbations of heterochromatin, including gain of euchromatic marks and aberrant distributions of repressive marks such as H3K27me3 and promoter DNA methylation. Genome-wide profiling of chromatin and transcription reveal modified epigenomic landscapes in cancer cells and a significant degree of aberrant gene activity from the inactive X chromosome, including several genes involved in cancer promotion. We demonstrate that many of these genes are aberrantly reactivated in primary breast tumors, and we further demonstrate that epigenetic instability of the inactive X can lead to perturbed dosage of X-linked factors. Taken together, our study provides the first integrated analysis of the inactive X chromosome in the context of breast cancer and establishes that epigenetic erosion of the inactive X can lead to the disappearance of the Barr body in breast cancer cells. This work offers new insights and opens up the possibility of exploiting the inactive X chromosome as an epigenetic biomarker at the molecular and cytological levels in cancer.